Unform in Bandwith of the Conditional Distribution Function with Functional Explanatory Variable: The Case of Spatial Data with the K Nearest Neighbour Method - Wahiba Bouabsa (Ekonometria)
In this paper the author introduced a new conditional distribution function estimator, in short (cdf), when the co-variables are functional in nature. This estimator is a mix of both procedures the k Nearest Neighbour method and the spatial functional estimation.(original abstract)